2009
DOI: 10.4049/jimmunol.182.1.111
|View full text |Cite
|
Sign up to set email alerts
|

CD69+CD4+CD25− T Cells, a New Subset of Regulatory T Cells, Suppress T Cell Proliferation through Membrane-Bound TGF-β1

Abstract: The underlying mechanisms of tumor-induced immune suppression need to be fully understood. Regulatory T (Treg) cells have been shown to play an important role in tumor immune escape. Until now, many subsets of Treg cells have been described that can suppress T cell response via different mechanisms. CD69 is generally regarded as one of the activating markers; however, recent studies show that CD69 may exert regulatory function in the immune response. In this study, we have identified tumor-induced CD69+CD4+CD2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
165
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(177 citation statements)
references
References 42 publications
5
165
0
7
Order By: Relevance
“…5C). This observation is particularly interesting due to the regulatory role recently attributed to cells expressing CD69 [38,39]. Nevertheless, this increase in CD69 expression was not restricted to T-cells coexpressing IFNg and IL-10, since it was also expressed in about 40% of CD4 + Foxp3 -…”
Section: Discussionmentioning
confidence: 85%
“…5C). This observation is particularly interesting due to the regulatory role recently attributed to cells expressing CD69 [38,39]. Nevertheless, this increase in CD69 expression was not restricted to T-cells coexpressing IFNg and IL-10, since it was also expressed in about 40% of CD4 + Foxp3 -…”
Section: Discussionmentioning
confidence: 85%
“…Tumor-induced CD69C CD4CCD25neg T cells have been claimed to be a new subset of regulatory T cells, since they are not Foxp3C, but express membrane-bound TGF-1 and can suppress T cell proliferation in a cell-cell contact manner. 24 Therefore, CD69C T cells could play a major role in the transition from a renal tumor controlled by immune cells to a tumor which evades immune control. A high expression of CD69CCD25neg T cells was found in chronic pancreatitis as well as in pancreatic ductal adenocarcinoma (associated with nodal invasion and higher grading) and L1CAM/ CD171 expression of tumor cells reduced proliferation, diminished CD25 expression and elevated CD69 expression in effector T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Next, to further characterize the Treg-of-B1a cells, we used a number of molecules reported to be associated with the functions of Treg cells. [22][23][24][25][26][27][28][29][30] We found that Treg-of-B1a cells expressed a series of surface molecules, including ICOS, PD-1, GITR, OX40, IL-10R and TNFR2 (Figure 3b). Among them, ICOS, GITR, IL-10R and PD-1 were expressed at higher levels Therefore, B-1a cells are the major IL-10-producing cell population present in the steady-state peritoneal cavity, and they spontaneously produce IL-10 without any stimulation.…”
Section: B-1a Cells Convert Naive Cd4 1 T Cells Into Foxp3 2 Treg Cellsmentioning
confidence: 92%